A fusão dos três maiores bancos privados nacionais (BES, BCP, BPI) - Palhinha, Nuno Gonçalo Santos (2015)
In the current adverse economic climate in which we are living, there is the question of how national banks will outline the medium and long term strategy to compete with the other players on a global scale, particularly in high-growth markets that are not saturated. The internationalization processes of the operations of national banks, namely the direct implementation of banks in the markets, have been mainly focused on markets where the Portuguese communities are, including the Portuguese-Speaking African Countries (PALOP). Given the small size of the domestic market, the national market has structured its organic dimension to that same market. One way to position the national banks on a global scale can be achieved by increasing the size of the structure of domestic banks. One of the used methods focuses on the merging of institutions as it allows to achieve synergies that lead to gains in market efficiency, and increase the return to the shareholders. It is within this scope that the study of the merger of the three largest domestic private banks – BES, BCP and BPI - is developed. This is a real case of the Portuguese financial sector, in which its individual predictable evolution, the merger and its effects, specifically the value created for the shareholders are analyzed. With the merger, which is the object of this study, a major national player shall be created which will allow the increase of the possibility of accessing to financing in international markets, the financing of the national real economy and the introduction of a strong competitive player in the markets in which it will operate.